Urban Resilience and Ecosystem Services: How Can Be Integrated in the Case of Istanbul - Sultanbeyli District? - Tezer, Azime; Yaman, Zeynep Deniz; Altun, Ayse Ozyetgin; Albayrak, Ilke (TeMA - Journal of Land Use, Mobility and Environment, 2012)
As estimated by UN, in 2030, 95 % of population growth will result from urban areas while a few metropolitan areas of rapidly growing developing countries will absorb much of this growth. Due to the accelerated urban growth and uncontrolled urban dispersion through naturally significant areas, sustainable urban growth management becomes a critical urban development policy for the global agenda. Istanbul has been attracting much of the internal migration with a dramatic urban growth process since 1950s and Istanbul Province, with over 12 million people, in 2010 is the most populated city of Turkey. Sultanbeyli, as a unique case for informal housing development in Istanbul, expanded like mushrooming after 1980’s and located itself on the largest drinking water source of Istanbul: the Omerli Watershed. The population of Sultanbeyli District grew from 82,298 (1990 census) to 272,758 people (2007 census) (TUIK, 1990;2007): more than threefold increase in less than two decades with consequent environmental degradation, uncontrolled ground water pumping, lack of drinking and waste water infrastructures. These endanger the well-being of the environment and of the society. On the other hand, the serious poverty problem is the main concern in Sultanbeyli for urban resilience (UR) which can be defined as the degree to which cities are able to tolerate alteration before reorganizing around a new set of structures and processes and which can be measured by how well a city can simultaneously balance ecosystem services (ES) and human functions (Resilience alliance, 2007). <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-ansi-language: EN-GB; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">This paper aims to discuss how to integrate ecosystem services and resilience theory which will be essential to resolve the problems reflected by social, economic and administrative characteristics of Sultanbeyli District to enhance its urban resilience capacity in Istanbul.